Impact of Light with Different Spectra on the Photosynthetic Activity of Cucumber Plants under Fusarium Wilt - Kabashnikova, Liudmila; Domanskaya, Irina; Molchan, Olga; Pashkevich, Lyubov; Dremuk, Irina; Martysiuk, Hanna; Viks, Tatsiana (Global Journal Of Botanical Science, 2022)
The photosynthetic activity of 28-day-old cucumber plants of the Kustovy variety formed under LED illumination with the predominance of red light (RL) or far red light (FRL) and infected with the fungus Fusarium oxisporum sp. (F.ox.) was studied. The predominance of RL or FRL contributed to an increase in the content of chlorophyll and carotenoids per dry leaf weight compared to the plants grown under white light (WL). In the infected plants grown under WL and RL regimes, an increase in the total content of chlorophyll and carotenoids was observed relative to healthy plants, and a decrease in the same parameters for FRL was noted. In healthy cucumber leaves grown under RL and FRL regimes, an increase in the activity of photosystem (PS)1 and PS2 in comparison with WL was observed. Infection of cucumber plants grown under WL did not cause any changes in the functional parameters of PS2 against the background of a slight reduction in PS1 complexes. Under RL and FRL regimes, a decrease in the photochemical activity of PS 1 and PS 2 in infected leaves was noted. The activity of ascorbate peroxidase - one of antioxidant enzymes in chloroplasts decreased in healthy cucumber leaves under RL and FRL compared to WL and increased in infected leaves compared to the healthy ones under all light regimes, especially strongly under RL. The results obtained demonstrate different response mechanisms for cucumber chloroplasts to the infection with a fungal pathogen, depending on the light conditions of growing.